واقع التنمية البشرية في سورية وفق مؤشرات دليل التنمية البشرية للعام 2012 (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2017)
تتطلب التنمية البشرية في سورية التركيز على مجموعة من الأولويات الأساسية أهمها تحقيق المساواة والعدالة الاجتماعية، فلها قيمة معنوية، وضرورية لتوسيع الإمكانات التنموية، حيث لا استمرار في التقدم بالتنمية البشرية مع انعدام المساواة والفوارق بشكل عام أو بحسب النوع بشكل خاص في مؤشرات التعليم والصحة والدخل حتى وإن لم تكن آثارها واضحة في المجتمع، حيث حققت سورية تقدماً في مجال التنمية البشرية خلال الفترة 1980-2012 فقد ارتفع مؤشر دليل التنمية البشرية (0.147)، ورغم اهتمام سورية بالتعليم والصحة وتوفيرها لجميع شرائح المجتمع السوري إلا أن تصنيفها وفق مؤشرات دليل التنمية البشرية الصادر عن هيئة الأمم المتحدة تنمية بشرية متوسطة، وجاء ترتيبها حسب البلدان 116/186، وتراجعت نقطتين حسب ترتيب البلدان وفق دليل الفوارق حسب النوع 118/186وقد بلغ الفقدان الكلي(20.4%) وفق دليل التنمية البشرية المعدل عامل عدم المساواة في (التعليم، الصحة، الدخل). Human Development in Syria requires a focus on a set of core priorities most important achievement of equality and social justice , they have sentimental value , and necessary to expand the development potential, as there is continued progress of human development with inequality and differences in general or according to the particular type of education , health and income indicators , even if its effects were not visible in the community, Where Syria has made progress in the field of human development during the period 1980-2012 was the HDI index ( 0.147 ), although Syria's interest in education, health and provided to all segments of the Syrian society , however, classified according to the human development index indicators published by the United Nations body medium human development , the ranking countries according to 116/186 , and fell two points according to the ranking of countries according to differences guide by genre 118/186 has reached the overall loss ( 20.4 % ), according to the human development Index average inequality factor in the (education, health , income ) .